1992
DOI: 10.1523/jneurosci.12-01-00056.1992
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate uptake disguises neurotoxic potency of glutamate agonists in cerebral cortex in dissociated cell culture

Abstract: The pharmacological properties of glutamate agonists were compared in astrocyte-rich and astrocyte-poor cultures derived from embryonic rat cerebral cortex. The object of this investigation was to determine the extent to which glutamate uptake might influence the receptor-mediated neurotoxic actions of these compounds. In astrocyte-rich cultures, using 30 min exposures, we observed that the potencies of the poorly transported agonists NMDA (35 microM) and D-glutamate (89 microM) were higher than that of L-glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
150
3
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(167 citation statements)
references
References 27 publications
10
150
3
4
Order By: Relevance
“…First, the high-capacity glutamate (Bergles and Jahr, 1998) and GABA- (Chatton et al, 2003) uptake systems in astroglia with processes in proximity to synapses would decrease the synaptic dwell times of either glutamate or GABA released into the synapse. This alone might increase spike rates, enabling faster signaling and reducing neuronal glutamate excitotoxicity (Rosenberg et al, 1992). However, the finding that addition of glia-conditioned medium reproduced all but the glutamate-stimulated effects indicates that diffusible trophic factors released by astroglia promote the baseline increases in spike rates.…”
Section: Discussionmentioning
confidence: 99%
“…First, the high-capacity glutamate (Bergles and Jahr, 1998) and GABA- (Chatton et al, 2003) uptake systems in astroglia with processes in proximity to synapses would decrease the synaptic dwell times of either glutamate or GABA released into the synapse. This alone might increase spike rates, enabling faster signaling and reducing neuronal glutamate excitotoxicity (Rosenberg et al, 1992). However, the finding that addition of glia-conditioned medium reproduced all but the glutamate-stimulated effects indicates that diffusible trophic factors released by astroglia promote the baseline increases in spike rates.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells are a source of glutamate in themselves, since previous reports showed that cultured Schwann cells secrete glutamate (Wu et al, 2005), although the significance of glutamate secretion is unknown. In the nervous system, the importance of glutamate metabolism has previously been discussed mostly in relation to excitotoxicity and/or glutamatergic neurotransmission (Rosenberg et al, 1992). In the CNS, glutamate is metabolized to glutamine only in astrocytes (Levy, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In cultures of cerebral cortical tissue from embryonic rats, 50% of neurons die within 24 h when exposed to 4 lM of glutamate for 30 min in the absence of glial glutamate uptake. The same neuronal mortality requires 205 lM of glutamate in the presence of astrocytes in the culture (Rosenberg et al 1992). Given that glutamate levels in perilymph may reach 40 lM following ischemia as noted above (Hakuba et al 1997), a requirement for glutamate uptake by the supporting cells seems eminently necessary to protect potentially glutamate-sensitive cochlear nerve cells from damage.…”
Section: Role Of Glast In Prevention Of Excitotoxicitymentioning
confidence: 94%